Hydronic heating systems: transient modelling, validation and load matching control - Zaheer-Uddin, M.; Monastiriakos, P. (International journal of energy research, 1998)
A dynamic model of a hydronic heating system is developed. The system consists of a boiler, baseboard terminal units, domestic hot water (DHW) heat exchanger coil and an environmental zone. The model is described by a set of time varying nonlinear coupled differential equations. Predicted responses from the model are compared with the measured data gathered on an on–off controlled hydronic heating system installed in an apartment building. Results show that the model predictions compare well with the field data. Using this validated model, feedback controllers are designed to achieve better regulation of zone air temperature, boiler water temperature and DHW temperature. A load tracking setpoint control strategy is proposed to regulate boiler temperature as a function of outdoor air temperature. Results showing the simulated responses of the system with the designed controllers subject to step changes in space heating and DHW loads are given. © 1998 John Wiley & Sons, Ltd.